Às brincas ou às ganhas? Não dá-ses scaps: o poder da linguagem em sua forma de ação social e intencional no jogo de bolinhas de gude - Paula, Regina Aparecida Milléo de (2004)
The purpose of this study of the terms and statements used on the game of gamble is to show, with the "ludic", what involves the production of the enunciation: presupposition, intention, belief, representation, adhesion, the power of changing interpretations and actions of the speaker. I focus changes and effects on the sense, creation and semantic evolution associating to terms utilizes in this game, terms that cause mythic and linguistic worlds to melt. The practice of this enunciation, the game inside the game, makes the symbolical processes become able to be used within the match and the such expected victory, with the subordination of the adversary, not only with the manual ability and aim, but also with the capability, the power of regulating the behavior by using the speech. I postulate that theses acts own an "ilocucionary" power that makes the "ludic" action of the language an art that transits between the semantic and pragmatic field